Macroeconomic and monetary policy issues in Indonesia - Hossain, Akhand Akhtar (Abingdon, Oxon : Routledge, 2012)
'Since gaining independence in 1949, Indonesia experienced serious economic and political problems during the 1950s and 1960s, before entering a three-decade-long period of rapid economic growth until the 1990s. In response to the financial crisis of the late 1990s, Indonesia undertook a wide range of economic and financial reforms. Drawing on empirical research, this book presents a comprehensive empirical study on the key macroeconomic relations and monetary policy issues in Indonesia. The book analyses monetary, fiscal and exchange rate policies, looking at their interactions and impacts on the economy, as well as discussing how macroeconomic management for monetary and financial stability is important for sustained economic growth. In addition to the use of the data from the 1970s, earlier data from the 1950s is used to analyse macroeconomic policies and issues in a historical context. Furthermore, statistical and econometric techniques are positioned alongside general empirical results to supplement descriptive discussion on macroeconomic and monetary developments.'--Publisher's description.
Macroeconomic developments, policies and issues : an historical overview from a political economy perspective -- Sources of economic growth -- Household consumption behaviour -- Sources and dynamics of inflation -- Inflation and inflation uncertainty -- Monetary policy and stability of the narrow money-demand function -- Export trends, structure and determinants -- Import trends, structure and determinants -- Determinants of the real exchange rate -- Exchange rates, capital flows and monetary policy -- Inflation targeting : an assessment of design, conduct and performance -- Fiscal policy and sustainability.
Includes bibliographical references (p. [365]-389) and index.
Keywords: Monetary policy -- Indonesia; Indonesia -- Economic policy